GREEN FINANCING : LITERASI KEUANGAN PEREMPUAN PENENUN “KRE ALANG” DALAM UPAYA MENINGKATKAN KINERJA KEUANGAN YANG BERKELANJUTAN - Sri Andriani; Nurasia Nurasia (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2026)
Sustainability is an issue that continues to be studied in order to create a balance between the environmental and industrial ecosystems. MSMEs, as one of the drivers of the Indonesian economy, are also directed to be able to create sustainable products, one of which is through green financing. However, in reality, the implementation of green financing by MSMEs is still relatively low. This study uses a qualitative approach by conducting interviews, observations, and documentation studies on MSMEs in Sumbawa, NTB, specifically among Kre' Alang artisans, a typical Sumbawa woven cloth. The results show that the level of green financing literacy among MSMEs in Poto Village, Sumbawa Regency is still very low. Furthermore, accessibility to green financing is also limited due to the lack of socialization and unmet requirements. This results in difficulties in evaluating the sustainable financial performance of woven cloth artisans.